Annexing energy : exploiting and preventing the development of oil and gas in the occupied Palestinian territory - Power, Susan (Ramallah Al-Haq, 2015)
Israel has forced a naval closure of the Gaza Strip as part of its energy security policy. The El-Arish pipeline and Mari-B gas platform are key Israeli strategic assets for its entire gas distribution network requiring stringent security measures. The Mari-B platform is located only 13 nautical miles from Gaza’s coast and the El-Arish pipeline runs across the entire Palestinian coast at 13 nautical miles connecting Ashkelon in Israel to El-Arish in Egypt. Since 2000, the year that Mari-B was first discovered, Israel has forced the closure of the Gaza Maritime Zone preventing Palestinian fishing and recreational use beyond distances of 6 nautical miles.  During this time American and Israeli gas companies have illegally exploited Palestine’s contiguous gas resources. Under customary international law joint cooperation is required for the development of joint geological resources. However, in 2012 United States corporation Noble Energy and Israeli corporation Delek Drilling, with approval from the State of Israel, rapidly exploited the Noa field from the Israeli side violating customary international law. The accelerated rate of gas production from the Noa well means that the entire resource is more than likely damaged beyond use. Commenting on the report, Shawan Jabarin, General Director of Al-Haq warned, “the exploitation and destruction of Palestinian gas resources represents a manifest violation of international law and may amount to the war crime of pillage. While the destruction of property not warranted by military necessity may amount to a grave breach of the Geneva Conventions.”
1. Introduction -- 2. Annexing natural resources in the OPT -- 3. Blocking the development of Palestine gas: a twisted play of politics -- 4. Israel's exploitation of Palestine gas -- 5. Forcibly closing the Gaza Strip to protect Israel's platforms and pipelines -- 6. Israel's gas distribution infrastructure -- 7. Oil in the occupied territory --   8. Legal analysis -- 9. Legal consequences for violations of international law -- 10. Conclusion -- 11. Recommendations
Includes Bibliographical References and Annexes
Keywords: Natural resources; NATURAL RESOURCES; PETROLEUM; NATURAL GAS; GAS PIPELINES; INTERNATIONAL LAW; GAZA STRIP; PALESTINE; ISRAEL; ARAB-ISRAELI CONFLICT; ECONOMIC ASPECTS